Photoinduced formation of flavin radicals in BLUF domains lacking the central glutamine. (6th May 2015) - Fudim, Roman; Mehlhorn, Jennifer; Berthold, Thomas; Weber, Stefan; Schleicher, Erik; Kennis, John T. M.; Mathes, Tilo
<x xml:space="preserve">Abstract</x> Blue light receptors using FAD (BLUFs) facilitate blue light‐induced signal transduction via light‐induced rearrangement of hydrogen bonds between the flavin chromophore and a conserved glutamine side chain. Here, we investigated the photochemistry of the BLUF domain Slr1694 from Synechocystis sp. in which the glutamine side chain was removed. Without the glutamine, no red‐shifted signaling state is formed, but light‐induced proton‐coupled electron transfer between protein and flavin takes place similarly as for the wild‐type protein. However, the lifetime of the neutral flavin semiquinone–tyrosyl radical pair is greatly prolonged from < 100 ps to several nanoseconds, which indicates that the formation of radical intermediates drives the hydrogen bond rearrangement in BLUF photoactivation. Moreover, glutamine plays a central role in the molecular organization of the hydrogen bond network in the flavin‐binding pocket, as its removal enhances electron transfer from tyrosine to the excited flavin, and enables competing electron transfer from a nearby tryptophan.